48 RANDOMIZED CONTROLLED TRIAL OF ABLATION FOR BARRETT'S ESOPHAGUS. (1st March 2005) - Dulai, G.; Jensen, D.; Cortina, G.; Ippoliti, A.
Abstract : Background: Endoscopic ablation of Barrett's esophagus has been described using a combination of high dose proton pump inhibitors and a variety of modalities for thermocoagulation. Randomized comparisons of ablation strategies have not been published. Methods: Referred subjects were screened to identify those with 2-7 cm of Barrett's esophagus without high grade dysplasia or cancer. Included subjects received pantoprazole 40 mg twice daily, followed by randomization to treatment with argon plasma coagulation (APC) versus multipolar electrocoagulation (MPEC). The primary outcome measure was number of treatment sessions to endoscopic ablation. Results: 235 subjects were screened, and 52 randomized. The mean length of Barrett's esophagus was 3.1 cm in MPEC versus 4.0 cm in APC (p = 0.03), but treatment groups were otherwise similar with regard to baseline characteristics. The mean number of treatment sessions to endoscopic ablation was 2.9 for MPEC versus 3.8 for APC (p = 0.04) in an intention to treat analysis, though p = 0.249 after adjustment for difference in Barrett's esophagus length. The proportions achieving ablation above the gastroesophageal junction endoscopically were 88% MPEC versus 81% APC (p = 0.68) and histologically 81% MPEC versus 65% APC (p = 0.21). The mean time per 1st treatment session was 6 minutes with MPEC versus 10 minutes with APC (p = 0.01) in per protocol analysis. There were no serious adverse events, but transient moderate to severe upper gastrointestinal symptoms occurred post-MPEC in 8% versus 13% post-APC (p = 0.64). Conclusions: Although there were no statistically significant differences, ablation of Barrett's esophagus with pantoprazole and MPEC resulted in numerically fewer treatment sessions and a greater proportion of subjects achieving endoscopic and histologic ablation than treatment with pantoprazole and APC.